Potensi Beberapa Sayuran Indigenous Bali sebagai Pangan Fungsional - Widarta, I Wayan Rai; Suter, I Ketut (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 2 (2022)DO - 10.24843/JITPA.2022.v07.i02.p03, 2022)
Vegetables are a source of dietary fiber, minerals, vitamins and antioxidants which are very important for health. The purpose of this study was to obtain the characteristics of the chemical components and bioactive compounds of several local indigenous Balinese vegetables (Kejompot leaf, Banana stem, Pumpkin leaf, and Gonda) in an effort to use them as functional food. The study was conducted using a completely randomized design (CRD) with the treatment of vegetable types and was repeated 4 times. Data were analyzed descriptively and presented in the form of tables and graphs. Parameters observed included: dietary fiber, water content, levels of Ca, Fe, Zn, total phenol, total flavonoid, vitamin C, and antioxidant activity. The results showed that local indigenous Balinese vegetables have the potential as functional food, especially Kejompot which contains higher bioactive components and antioxidant activity than other vegetables.